Trends of Gamification Tools in Teaching Arabic in the Era of Globalization: A Literature Review Study: اتجاهات وسائل التلعيب في تعليم اللغة العربية في عصر العولمة: دراسة قائمة على مراجعة الأدبيات - Farha Fuada; Andini Nuraisyah; Husnul Hafiza Rahma; Kisno Umbar; Khabib Syaikhu Rohman (UIN Raden Mas Said Surakarta, 2025)
Gamification has emerged as one of the most prominent methods in Arabic language teaching in the era of globalisation, particularly in response to the challenges posed by learners' poor academic achievement and lack of engagement with traditional teaching methods. This study aims to explore the development of gamification trends and identify the most commonly used gamification-based teaching methods in Arabic language teaching. The research relied on a literature review methodology, analysing eight relevant articles selected through a systematic screening process. The results reveal that gamification has been used at different educational levels, from primary school to higher education, and has covered a wide range of language skills, including listening, speaking, reading, writing, vocabulary acquisition, and grammar mastery. A total of 19 gamification-based digital tools were identified, including Memrise, Duolingo, Quizizz, and Kahoot, which emerged as the most used by Arabic language learners. The study concludes that gamification is not only an innovative and engaging approach, but also has great potential to improve Arabic language education. These findings are expected to provide teachers, curriculum designers, and researchers with valuable insights for developing more effective and contextually relevant gamification-based learning strategies.